Assessment of the Microbiological Quality of Public Restaurants and Street Vended Ready-To-Eat “Koshari” Meals - Mohamedin, Attiya; Michel, Magdy; Tolba, Marwa (International Journal of Applied Sciences and Biotechnology, 2015)
Ninety ?Koshari? meals samples were collected from some restaurants and street vendors located in six public quarters in central Cairo, to determine the microbiological quality of them directly after cooking and preparing and after 4 & 8 hrs of storage at room temperature. These samples examined for aerobic bacteria, Esherichia coli and coagulase positive Staphylococci to conduct a preliminary microbial risk assessment for them in” koshari “meals. According to the CDPH (2009) only 53 samples (59%) were of satisfactory microbiological quality for Aerobic plate count (APC) and 81 samples (90%) were positive for E. coli cells and 58% of them (47 samples) are acceptable quality. About coagulase positive S. aureus, 28 samples (31.1 %) were positive and only 60.7% of them (17 samples) of satisfactory microbiological quality.Moreover, the percentage of unacceptable microbiological quality samples tested (potentially hazardous) reached to 36 samples (40%), 29 samples (32.2%), and 17 samples (18.9%) for APC, E. coli and S. aureus respectively, after 8 hrs of storage at room temperature. This study reveals that “Koshari” meals sold on the public areas are unwholesome and could be a potential source of food-borne bacteria pathogens if not properly handled. Option might be to suggest that the product should be consumed within short time of purchase in these places. Improvements in processing and handling are required and the need of food-borne bacteria disease surveillance indicated. In addition, it was evident that the Egyptian Food Code needed new legal revisions. Int J Appl Sci Biotechnol, Vol 3(3): 452-458